The Combination of Human Urinary Kallidinogenase and Mild Hypothermia Protects Adult Rats Against Hypoxic-Ischemic Encephalopathy-Induced Injury by Promoting Angiogenesis and Regeneration - Gao, Xiaoya; Xie, Haiting; Zhu, Shuzhen; Yu, Bin; Xian, Ying; Ouyang, Qian; Ji, Yabin; Yang, Xiaohua; Wen, Chunyan; Wang, Penghua; Tong, Yufeng; Wang, Qing (Frontiers in Aging Neuroscience, 2018)
Objectives: Human Urinary Kallidinogenase (HUK) is a tissue kallikrein that plays neuroprotective role in ischemic conditions via different mechanisms. Mild hypothermia (MH) is another robust neuroprotectant that reduces mortality but does not profoundly ameliorate the neurological outcome in hypoxic-ischemic encephalopathy (HIE) patients. However, whether the combination of HUK and MH can be used as a promising neuroprotective treatment in HIE is unknown. Methods: One-hundred and forty-four adult Wistar rats were randomly divided into five groups: Sham, HIE, HUK, MH and a combination of HUK and MH treatment. The HIE rat model was established by right carotid dissection followed by hypoxia aspiration. The survival curve was created within 7 days, and the neurological severity scores (NSS) were assessed at days 0, 1, 3, and 7. Nissl staining, Terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL), immunofluorescent staining and western blotting were used to evaluate neuronal survival, apoptosis and necrosis, tight-junction proteins Claudin-1 and Zonula occludens-1 (ZO-1), vascular endothelial growth factor (VEGF), doublecortex (DCX), bradykinin receptor B1 (BDKRB1), BDKRB2 and Ki67 staining. Results: The combined treatment rescued all HIE rats from death and had a best survival curve compared to HIE. The Combination also reduced the NSS scores after HIE at days 7, better than HUK or MH alone. The combination of HUK and MH reserved more cells in Nissl staining and inhibited neuronal apoptosis and necrosis as well as significantly attenuated HIE-induced decreases in claudin-1, ZO-1, cyclin D1 and BDKRB1/B2 in comparison to HUK or MH treatment alone. Moreover, the combined treatment increased the expression of VEGF and DCX as well as the number of Ki67-labeled cells. Conclusions: This study demonstrates that both HUK and MH are neuroprotective after HIE insult; however, the combined therapy with HUK and MH enhanced the efficiency and efficacy of either therapy alone in the treatment of HIE, at least partially by promoting angiogenesis and regeneration and rescuing tight-junction loss. The combination of HUK and MH seems to be a feasible and promising clinical strategy to alleviate cerebral injury following HIE insult. Highlights: - The combination of HUK and MH distinctly reduces neurological dysfunction in HIE rats. - HUK enhances the neuroprotective effects of MH in HIE. - MH attenuates tight-junction disruption, upregulates the BDKR B1/2, DCX and cyclin D1. - The combination of MH and HUK enhances the expressions of MH/HUK mediated-BDKR B1/2, DCX, cyclin D1 and Ki67 positive cells.